Leaving surgical training: some of the reasons are in surgery. Issue 5 (7th February 2018) - Forel, Deanne; Vandepeer, Meegan; Duncan, Joanna; Tivey, David R.; Tobin, Stephen A.
Abstract : In 2014, the Royal Australasian College of Surgeons identified, through internal analysis, a considerable attrition rate within its Surgical Education and Training programme. Within the attrition cohort, choosing to leave accounted for the majority. Women were significantly over‐represented. It was considered important to study these 'leavers' if possible. An external group with medical education expertise were engaged to do this, a report that is now published and titled 'A study exploring the reasons for and experiences of leaving surgical training'. During this time, the Royal Australasian College of Surgeons came under serious external review, leading to the development of the Action Plan on Discrimination, Bullying and Sexual Harassment in the Practice of Surgery, known as the Building Respect, Improving Patient Safety (BRIPS) action plan. The 'Leaving Training Report', which involved nearly one‐half of all voluntary 'leavers', identified three major themes that were pertinent to leaving surgical training. Of these, one was about surgery itself: the complexity, the technical, decision‐making and lifestyle demands, the emotional aspects of dealing with seriously sick patients and the personal toll of all of this. This narrative literature review investigates these aspects of surgical education from the trainees' perspective.